Highly efficient crystallization of AlPO4-5 accelerated by a rotating hydrothermal synthesis route. Issue 42 (5th August 2019) - Xia, Kun; He, Zhechao; Zhou, Dan; Lu, Xinhuan; Xia, Qinghua
Abstract : Rapid crystallization of AlPO4 -5 accelerated by rotation accompanied by the conversion from five-coordinated Al to four-coordinated Al. Abstract : Compared with static hydrothermal synthesis, the crystallization rate of an AlPO4 -5 molecular sieve has been accelerated distinctly by a rotating hydrothermal synthesis route with obviously decreased crystal particle size, which is assumed to be ascribed to the increased nucleation centers, accelerated crystal nucleation and growth processes; five-coordinated Al is dominant in the initial reaction gel, and the assembly from amorphous Al species to long-range ordered crystals is mainly contributed by the conversion from five-coordinated Al to four-coordinated Al.